Plan de Mejora para los Procesos Administrativos de la Empresa Treblactec Tecnology S.A.S - Malaver Leon, Maria Camila; Morales Castillo, Leily Mayury (Universidad Antonio Nariño, 2021)
Our research consists of designing the continuous improvement plan for the administrative processes of the company Treblactec (Process Manual), a company that is dedicated to the commercialization of technological products and services, said company is new in themarket located in the city of Bogotá, Colombia.